Neutrophil–lymphocyte ratios in the prognostication of primary non-metastatic nasopharyngeal carcinoma - Liew, Kong Yew; Zulkiflee, Abu Bakar (Elsevier, 2018)
Introduction: Nasopharyngeal carcinoma is a geographically and racially variable disease which has a high incidence in Malaysia. Based on current concepts in tumour related inflammation the inflammatory marker, neutrophil–lymphocyte ratio was tested to find its relationship with prognosis in nasopharyngeal carcinoma. Objective: To investigate the effect of the neutrophil–lymphocyte ratio on prognosis in non-metastatic primary nasopharyngeal carcinoma patients and to further refine the cut off between high and low neutrophil–lymphocyte ratio values. Methods: The medical charts of patients with histologically confirmed nasopharyngeal carcinoma from 1st January 2005 until 31st December 2009 were reviewed retrospectively and theneutrophil–lymphocyte ratio was calculated to see if there was any association between their higher values with higher failure rates. Results: Records of 98 patients (n = 98) were retrieved and reviewed. Only neutrophil–lymphocyte ratio (p = 0.004) and tumor node metastasis staging (p = 0.002) were significantly different between recurrent and non-recurrent groups, with the neutrophil–lymphocyte ratio being independent of tumor node metastasis staging (p = 0.007). Treatment failure was significantly higher in the high neutrophil–lymphocyte ratio group (p = 0.001). Disease free survival was also significantly higher in this group (p = 0.000077). Conclusion: High neutrophil–lymphocyte ratio values are associated with higher rates of recurrence and worse disease free survival in non-metastatic nasopharyngeal carcinoma patients undergoing primary curative treatment.